Evolution of structural path indexing techniques in XML databases: A survey and open discussion - Su-Cheng, Haw; Chien-Sing, Lee (2008)
With the rapid emergence of XML as a data exchange and data transfer medium over the Web, querying XML data has become a major concern. Various optimization technologies, among them those based on XML, have been developed to solve query retrieval problems. In this paper, we suggest an indexing classification scheme and survey the existing path indexing techniques. We also analyze how each approach works, as well as its advantages and disadvantages. In addition, we discuss some of the current trends in indexing methods, which indicate a clear shift towards hybrid approaches. Hybrid systems open the possibility of balancing one technology's weakness with another technology's strengths.